Impact of covid-19 pandemic on physical interaction among university students in UTAR - Tan, Kai Wen (2023)
In the current post-pandemic stage in Malaysia, students are returning to their campuses for physical classes, which means that students will have to attend classes in a classroom in the university facilities. There are major academic changes in university class availability and content distribution, where academics, students and management teams in universities operate as a consequence of the virus’s growth and severity. This greatly affects the psychological habits and routines of a university student, as they develop new habits in their social life. Students who are used to online interactions during the pandemic may find it challenging to revert their social life back to normal. This research focuses on the impact of the pandemic on university students’ ability to interact and communicate with others physically. This research investigates students who have been engaging in online events or online interactions, and also students who have not.